PROBLEMATIKA DALAM PEMBELAJARAN BAHASA INGGRIS DI STAIN BENGKALIS - Roinah, Roinah (QUALITY, 2019)
This study aims to describe the problem of learning English in terms of internal factors and external factors in STAIN Bengkalis students. The researcher formulated the problem in the form of: a) how the description of the problem of learning English in terms of internal factors in STAIN Bengkalis students ?; b) how is the description of English learning problems seen externally in STAIN Bengkalis students? The research sample amounted to 310 respondents. Respondents were chosen randomly by simple random sampling technique. The research instrument used was a questionnaire. Before data collection, the instrument has been tested for validity and reliability for the validity of the data collected. The results of the study show; the picture of the problem of learning English is seen in terms of internal factors in STAIN Bengkalis students which are influenced by (1) attitudes towards learning; (2) learning motivation; (3) concentration of learning; (4) intelligence and learning success; (5) study habits; (6) ability to process learning materials and (7) ability to achieve. The description of English learning problems seen in terms of external factors in STAIN Bengkalis students is influenced by educators, namely lecturers who teach English that are less varied in teaching. Respondents were very aware that learning English was a necessity because English became an international language. From the questionnaire distributed to respondents the internal factors are more dominant in success in learning.Key words: Problems; learning; English.